Semi-empirical approach to characterize thin water film behaviour in relation to droplet splashing in modelling aircraft icing - Alzaili, Jafar S. L. (Cranfield University, 2012)
Modelling the ice accretion in glaze regime for the supercooled large droplets is one of the most challenging problems in the aircraft icing field. The difficulties are related to the presence of the liquid water film on the surface in the glaze regime and also the phenomena associated with SLD conditions, specifically the splashing and re-impingement. The steady improvement of simulation methods and the increasing demand for highly optimised aircraft performance, make it worthwhile to try to get beyond the current level of modelling accuracy. A semi-empirical method has been presented to characterize the thin water film in the icing problem based on both analytical and experimental approaches. The experiments have been performed at the Cranfield icing facilities. Imaging techniques have been used to observe and measure the features of the thin water film in the different conditions. A series of numerical simulations based on an inviscid VOF model have been performed to characterize the splashing process for different water film to droplet size ratios and impact angles. Based on these numerical simulations and the proposed methods to estimate the thin water film thickness, a framework has been presented to model the effects of the splashing in the icing simulation. These effects are the lost mass from the water film due to the splashing and the re-impingement of the ejected droplets. Finally, a new framework to study the solidification process of the thin water film has been explored. This framework is based on the lattice Boltzmann method and the preliminary results showed the capabilities of the method to model the dynamics, thermodynamics and the solidification of the thin water film.
Keywords: Thin Water Film Velocity; Water Film Thickness; Corona Breakup; Volume of Fluid Method; Splashing and Re-impingement; Lattice Boltzmann Method; Solidification